Nutrition, physical activity and lifestyle as important indicators for the body mass index in high school students - Lorik Ramaj; Sadete Hasani (Kazimierz Wielki University, 2021)
The purpose of this study was to investigate and analyze the problems of underweight, overweight and obesity in young people of high school in Drenas, respectively a sample of 150 adolescents (73 males and 77 females aged 17 years). The research was conducted in the physical education class, initially was performed measurement of weight and height then the questionnaire with 26 questions. Data were collected with the statistical program SPSS version 21.0, descriptive analysis was performed with (Mean and standard deviation), all variables were tested for normality, significant level (significant level p <0.05). Results of anthropometric characteristics, the average age was 17.2 years. Weight / kg for men was 59.4 kg for women 57.3kg the average for both genders was 58.3 (± 6.2) kg. Height / cm  males 1.68cm,  females 1.61cm the average of both genders was 1.64 (± 6.6) cm. BMI body mass index kg / m² in men 21.0, women 22.1, the average of both sexes 21.55 kg / m5. The results show that men have lower BMI (p> 0.05) 21.55 kg / m² than girls with 22.1 kg / m². Data showed underweight males are 12%, and females 10%. BMI Normal male 74%, and female 69%. Overweight males 11%, females 13% while a significant difference was observed between obese boys and girls (obese) males 3% and females 8%. The analysis of the questionnaire showed that small percentages are involved in collective or individual sports, the most pronounced participation in sports was identified: football, volleyball and basketball, and relatively satisfactory were physical activity in household activities. It is recommended to build outdoor fitness and sports gyms, as well as the opening of various sports clubs in this area, and to have more research in this area, to prove the institucions how important are places for sport and physical activities.